LEADERSHIP AS HERDING IN XENOPHON - Sandridge, Norman; Esposito, John (Science et Esprit, 2022)
The purpose of this paper is not so much to critique what Michel Foucault has to say on the idea of leadership as a form of herding, so much as to posit a different solution to the problems of the image of the shepherd-as-leader, offered by the other famous philosopher-student of Socrates, Xenophon of Athens. We consider leadership as herding in Xenophon, in his several works, but particularly in his Cyropaedia (The Education of Cyrus), a fourth-century BCE prose work that purports to tell us about (i) the life of Cyrus II (“the Great”) from his childhood education in the Persian system to his death and (ii) the great realization of Cyrus’s life, which is to have established the world’s first multinational empire. The reason for our focus on this work is simple: the self-justifying apologia that opens the Cyropaedia casts this King of Persia as the most remarkable herdsman-of-humans to have ever lived.